Evaluation of effectiveness of self-adhesive composites for amalgam repair with or without alloy primer, in terms of shear bond strength = Evaluación de la efectividad de los compuestos autoadhesivos para la reparación de amalgamas con o sin imprimación de aleación, en términos de resistencia al cizallamiento - Ayşe Şanal, Fatma
Purpose: The purpose of the present research was to evaluate the effectiveness of self-adhesive composites in amalgam repair as time-saving alternatives to universal bonding-universal composite materials, with or without the usage of Alloy Primer in terms of shear bond strength. Materials and Methods: Forty-two disc-shaped amalgam samples were prepared by condensing into 6×2 mm holes in acrylic resin blocks, sandblasted with 50 μm Al2O3 and randomly divided into 6 groups according to repair material [Constic (Group C), Fusio Liquid Dentin (Group FLD), Universal bonding+Universal composite (Group Control), Alloy Primer+Constic (Group APC), Alloy Primer+Fusio Liquid Dentin (Group APFLD), Alloy Primer+Universal bonding+Universal composite (Group APControl)]. After shear bond strength test, the fracture modes were determined under a digital microscope. Statistical analysis was performed using one-way analysis of variance and Tukey's post hoc test. Results: The highest shear bond strength values were obtained for Fusio Liquid Dentin, among the three repair materials when Alloy Primer was not applied (p<0.05). Usage of Alloy Primer increased shear bond strength values of the investigated repair materials to amalgam, except Fusio Liquid Dentin. Conclusion: Within the limitations of the present research, it can be concluded that; the investigated self-adhesive composite materials could be time-saving alternatives to the Universal bonding+Universal composite for the purpose of amalgam repair, in terms of shear bond strength. The clinicians could prefer Fusio Liquid Dentin self-adhesive composite material without Alloy Primer application for the purpose of amalgam repair in non-cooperative patients.